1974
DOI: 10.1288/00005537-197402000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and treatment of vocal cord paralysis

Abstract: One hundred eighty‐one patients with unilateral or bilateral vocal cord paralysis unrelated to laryngeal carcinoma or its therapy were studied. The orderly diagnostic profile used to delineate cause of the paralysis includes CBC, VDRL blood sugar profile, latex fixation and serum sampling for toxic heavy metals. The radiologic and endoscopic evaluation is done to completion unless contraindicated, to assess aspiration as well as to observe laryngopharyngeal structures which may cause the paralysis. This evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
1

Year Published

1976
1976
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 25 publications
2
58
1
1
Order By: Relevance
“…Injury to the RLN or vagus nerve may occur as a result of a wide range of etiology, including iatrogenic trauma, non-iatrogenic trauma, neoplasm, and systemic disease [1][2][3][4][5]. The lengthy course of the RLNs places them at high risk of injury, particularly the left nerve, which loops around the aorta.…”
Section: Causes Of Vocal Fold Immobilitymentioning
confidence: 99%
“…Injury to the RLN or vagus nerve may occur as a result of a wide range of etiology, including iatrogenic trauma, non-iatrogenic trauma, neoplasm, and systemic disease [1][2][3][4][5]. The lengthy course of the RLNs places them at high risk of injury, particularly the left nerve, which loops around the aorta.…”
Section: Causes Of Vocal Fold Immobilitymentioning
confidence: 99%
“…For traumatic BVCP Feehery [5] reported an incidence of 32.6 % from Henry ford hospital and 26.7 % from Jefferson hospital. Tucker et al [19] and Maisel [20] reported an incidence of 30 and 31.50 % respectively. The incidence of traumatic BVCP in our study (12.5 %) is less as compared to previous studies, possibly due to small sample size of the patients with BVCP.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of idiopathic BVCP is more erratic than for UVCP. In 1973 Bulteau [23] reported a highest incidence of 50 %; just a year later Maisel [20] reported the lowest incidence literature of 3.7 %. Such differences may be partly ascribed to the criteria used for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In weiteren Veröffentlichungen wird die differenzialdiagnostische Abklärung manifester Stimmlippenfunktionsstörun-gen dargestellt [5,31,50,67,74,81,84]. Aufgrund der Anamnese erfolgte bei weniger als 11% der Patienten dieser Untersuchungen die Zuordnung zur Ursache "Intubation".…”
Section: Kritischer Kommentar Aus Anästhesiologischer Sichtunclassified